THE MAKING OF PROMOTIONAL VIDEO OF TOURISM IN RUPAT ISLAND - Muhammad - Sabri (Politeknik Negeri Bengkalis, 2018)
The aim of this study was to make a video to promote Rupat Island to the international tourists as a tourism destination. The method used in this study was a descriptive research. There were several steps in making this video; starting from collecting the materials, creating the video script, shooting process, recording the voice for the video. converting the files, until editing the video. The result of this study is a promotional video narrated in English that contains both natural and cultural tourism objects and attractions in Rupat Island such as: Beting Aceh Beach, Lapin Beach, Makeruh Beach, Suku Akit Tradition, Mandi Safar Festival, Zapin Api Dance, etc. This video is expected to help the government of Bengkalis Regency in promoting Rupat Island as a tourism destination in the future.